Efficacy of dapagliflozin in heart failure with reduced ejection fraction according to body mass index. (29th July 2021) - Adamson, Carly; Jhund, Pardeep S.; Docherty, Kieran F.; Bělohlávek, Jan; Chiang, Chern‐En; Diez, Mirta; Drożdż, Jarosław; Dukát, Andrej; Howlett, Jonathan; Ljungman, Charlotta E.A.; Petrie, Mark C.; Schou, Morten; et al.
Abstract : Aims: In heart failure with reduced ejection fraction (HFrEF), there is an 'obesity paradox', where survival is better in patients with a higher body mass index (BMI) and weight loss is associated with worse outcomes. We examined the effect of a sodium–glucose co‐transporter 2 inhibitor according to baseline BMI in the Dapagliflozin And Prevention of Adverse‐outcomes in Heart Failure trial (DAPA‐HF). Methods and results: Body mass index was examined using standard categories, i.e. underweight (<18.5 kg/m 2 ); normal weight (18.5–24.9 kg/m 2 ); overweight (25.0–29.9 kg/m 2 ); obesity class I (30.0–34.9 kg/m 2 ); obesity class II (35.0–39.9 kg/m 2 ); and obesity class III (≥40 kg/m 2 ). The primary outcome in DAPA‐HF was the composite of worsening heart failure or cardiovascular death. Overall, 1348 patients (28.4%) were under/normal‐weight, 1722 (36.3%) overweight, 1013 (21.4%) obesity class I and 659 (13.9%) obesity class II/III. The unadjusted hazard ratio (95% confidence interval) for the primary outcome with obesity class 1, the lowest risk group, as reference was: under/normal‐weight 1.41 (1.16–1.71), overweight 1.18 (0.97–1.42), obesity class II/III 1.37 (1.10–1.72). Patients with class I obesity were also at lowest risk of death. The effect of dapagliflozin on the primary outcome and other outcomes did not vary by baseline BMI, e.g. hazard ratio for primary outcome: under/normal‐weight 0.74 (0.58–0.94), overweight 0.81 (0.65–1.02), obesity class I 0.68 (0.50–0.92), obesity class II/III 0.71 (0.51–1.00) ( P ‐value for interaction = 0.79). The mean decrease in weight at 8 months with dapagliflozin was 0.9 (0.7–1.1) kg ( P < 0.001). Conclusion: We confirmed an 'obesity survival paradox' in HFrEF. We showed that dapagliflozin was beneficial across the wide range of BMI studied. Clinical Trial Registration: ClinicalTrials.gov NCT03036124. Abstract : Key findings from the analyses of body mass index in the DAPA‐HF trial. BMI, body mass index; HFrEF, heart failure with reduced ejection fraction.